Crimean-Congo haemorrhagic fever: knowledge and practices of doctors at a tertiary care hospital in Lahore - Shahid, Hassan; Daud, Seema (International Journal Of Community Medicine And Public Health, 2017)
Background: Crimean-Congo haemorrhagic fever (CCHF) is a potentially fatal yet preventable zoonotic haemorrhagic disease which has consumed the lives of many health care workers in different regions of Pakistan over the past few years. There is neither a specific therapy nor an effective vaccine for the disease, which makes prevention the most rational approach towards CCHF. Hence, our main objective in this study was to determine the knowledge and practices of doctors regarding Crimean-Congo haemorrhagic fever (CCHF) at a tertiary care teaching hospital in Lahore. Methods: Non-probability convenience sampling was used to recruit the study sample (N=136). A structured questionnaire was used to collect data comprising of 35 multiple response questions pertaining to demographic information and knowledge and practice of the respondents regarding CCHF. Descriptive statistics was used to present data as numbers and percentage. Results: The study participants included 46 house officers, 69 post-graduate trainee/medical officers and 21 consultants. Among the respondents, 80% rated their knowledge regarding CCHF to be insufficient and 71% revealed that they did not feel confident while managing a patient of CCHF. While managing patients with active haemorrhage, 32% of our respondents either never or only sometimes used personal protective equipment. Nearly all study participants (93%) expressed the desire to acquire more education on CCHF in future. Conclusions: Knowledge of doctors regarding CCHF and compliance in terms of standard infection control protocols were inadequate.